Översättning i och med tvåspråkiga ordböcker - Gellerstam, Martin (LexicoNordica, 2004)
This paper discusses several important questions connected to the presentation of semantic information in bilingual dictionaries. When planning the compilation of such a dictionary, the authors must take several key decisions on problems related to transfer of the semantics of the source language to the target language. Their decisions on the handling of cases of polysemy and homonymy and the presentation of the equivalents of each entry have practical repercussions for the organisation of the dictionary. Taking as our point of departure a middle-size Lithuanian-Norwegian dictionary, with which we have some experience ourselves, we present some of the dilemmas typically encountered by lexicographers when compiling bilingual dictionaries.